A preliminary survey on edibles and medicinal plants used by Dusun of Kampung Pinolobu, Kadamaian, Kota Belud, Sabah, Malaysia - Fadzilah Awang-Kanak; Azlinah Matawali; Nur Ramziahrazanah Jumat; Sitty Nur Syafa Bakri (Penerbit UMS, 2021)
This paper provides a brief enumeration of 22 species of plants and four species of fungi as wild edibles, and 13 species of plants that have been used for medicinal purposes by Dusun people of Kampung Pinolobu, Kadamaian, Kota Belud, Sabah. Seven informants were selected using snowball sampling technique, and data on edibles and medicinal plants were collected using semi structured interviews. This study reveals how Dusun people of Kampung Pinolobu used 13 species of medicinal plants to treat ailments and diseases like fever, high blood pressure, flatulence, rheumatism, cold, cough, and gastric pain. The flower of Carica papaya and fruit of Passiflora foetida are used for high blood pressure treatment, leaves of Manihot esculenta serve two purposes, as traditional vegetables and also consumed to avoid flatulence. Decoction made from the root of Ficus septica was given to women during postpartum recovery as they believed that it would help to keep the body warm, treat headache, and stomach pain. Paste made from leaves of Melastoma malabathricum is used to treat wounds. Meanwhile crushed leaves of Hibiscus rosa-sinensis, root decoction of Imperata cylindrica, sap from Calamus sp. are used to treat high fever, crushed leaves of Hibiscus rosa-sinensis is also used to subside carbuncle. Decoction of young leaves of Psidium gujava and Leucosyke capitella are used to treat stomach pain. Meanwhile decoction of crushed tuber of Curcuma longa is used to treat gastric pain.